Molecular characterization of breast cancer cell lines by clinical immunohistochemical markers - Mota, André de Lima (Oncol Lett, 2017)
Breast cancer is the leading cause of cancer mortality in females worldwide. Studies based on gene expression profiles have identified different breast cancer molecular subtypes, such as luminal A and B cells, cancer cells that are estrogen receptor (ER) and/or progesterone receptor (PR) positive, human epidermal growth factor 2 (HER2)-enriched cells, cancer cells that exhibit an overexpression of the oncogene HER2, and triple-negative cells, cancer cells that are negative for ER, PR and HER2 expression. Immunohistochemistry is the most common type of method used for the identification of these molecular subtypes, through the identification of specific cell receptors. The present study aimed to evaluate the ER, PR and HER2 receptor expression in human breast cancer cell lines, and to classify the corresponding molecular subtype comparing two alternative methods. In the present study, a panel of human mammary carcinoma cell lines: BT-20; Hs578T; MCF-7; MCF-7/AZ; MDA-MB-231; MDA-MB-468; SKBR3; and T47D were used. Immunohistochemical and immunocytochemistry assays were used to characterize the breast cancer subtypes of these cell lines according to the expression of ER, PR and HER2 receptors. The results revealed the molecular characterization of this panel of breast cancer cell lines, using the differential expression of classical and clinically used markers in concordance with previous studies. In addition, these data are important for additional in vitro studies of these specific receptors.